2018
DOI: 10.1002/acm2.12252
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric modulated arc therapy treatment planning of thoracic vertebral metastases using stereotactic body radiotherapy

Abstract: Purpose/ObjectivesTo retrospectively evaluate the plan quality, treatment efficiency, and accuracy of volumetric modulated arc therapy (VMAT) plans for thoracic spine metastases using stereotactic body radiotherapy (SBRT).Materials/MethodsSeven patients with thoracic vertebral metastases treated with noncoplanar hybrid arcs (NCHA) (1 to 2 3D‐conformal partial arcs +7 to 9 IMRT beams) were re‐optimized with VMAT plans using three coplanar arcs. Tumors were located between T2 and T7 and PTVs ranged between 24.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Just as Steven et al [8] concluded, IMRT techniques, by virtue of a greater dose conformity, are potentially able to reduce toxicity to OARs but not to improve survival outcomes [22]. These techniques have already been effectively tested in other clinical scenarios demanding a significant sparing of some OARs, e.g., spinal cord or urethra, similarly located within a surrounding radiotherapy target [23][24][25], or for reirradiation [26]. We know that other radiotherapy techniques are equally effective in the treatment of cutaneous targets [27][28][29][30], but their use is less suitable for highly complex clinical situations such as the present one.…”
Section: Discussionmentioning
confidence: 99%
“…Just as Steven et al [8] concluded, IMRT techniques, by virtue of a greater dose conformity, are potentially able to reduce toxicity to OARs but not to improve survival outcomes [22]. These techniques have already been effectively tested in other clinical scenarios demanding a significant sparing of some OARs, e.g., spinal cord or urethra, similarly located within a surrounding radiotherapy target [23][24][25], or for reirradiation [26]. We know that other radiotherapy techniques are equally effective in the treatment of cutaneous targets [27][28][29][30], but their use is less suitable for highly complex clinical situations such as the present one.…”
Section: Discussionmentioning
confidence: 99%
“…It has not been the purpose of this study to compare VMAT with other treatment techniques. However, several previous studies have reported significantly shorter beam-on times using VMAT compared to other techniques such as static intensity modulated radiotherapy (IMRT) [25] , [26] , [27] , [28] . The use of VMAT and FFF-beams is an ideal combination to obtain very short beam-on times and minimize the risk of unwanted patient movements.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of high-dose treatments like stereotactic body radiation therapy (SBRT) [8] raises the important questions about the updated role of RT in MM management. Although increasingly effective [9], some reports highlight that modern radiation techniques, like VMAT (volumetric modulated arc therapy), can increase the risk of lymphopenia by irradiating large volumes of tissue with low doses of radiation [10]. Cytopenias, including neutropenia, have been associated with worse outcomes in MM [11].…”
Section: Introductionmentioning
confidence: 99%